Food processing equipment guide - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Small-scale food processing edited by Peter Fellows and Ann Hampton 158pp ISBN 185339 108 5 Pbk price UKL30.00 published by CTA and Intermediate Technology Publications Available from CTA